APLIKASI GAME SURVIVAL HOROR 3D PENCEGAHAN PENCULIKAN ANAK REMAJA BERBASIS DEKSTOP - Ade Susianti, Febrina; Vitianingsih, Anik Vega; Choiron, Achmad; Cahyono, Dwi; Wikaningrum, Anggit (Universitas Budi Luhur, 2024)
The increase in child abduction cases in Indonesia highlights the need for a better understanding of the dangers of abduction among teenagers, especially abduction in online games. This occurs due to parents' lack of awareness of their children's gaming activities and also because children often seek social interaction through online games. Therefore, an educational approach is needed that involves teenagers and parents in understanding and preventing child abduction cases. The purpose of this research is to develop educational media through games using finite state machines (FSM) and forward chaining. FSM is used for the control system on the player, while forward chaining is used for the puzzle and puzzle system in making decisions based on information taken by the player. The research method uses the Multimedia Development Life Cycle (MDLC) method, which includes determining the application concept, 3-dimensional object design, material collection, application development, application testing, and application publishing. The results of the white box trial ran well, and the validation test was carried out on 30 respondents, with 83.8% stating that this game deserves to be an alternative learning media in self-defense from the crime of kidnapping teenagers.